PENERAPAN TEKNIK SEARCH ENGINE OPTIMIZATION (SEO) PADA WEBSITE COMPANY (Studi Kasus: www.sargentrack.com) - Rahma, Rindia Aulia; Mahmudin, Mahmudin (JURNAL TEKNIK INFORMATIKA UNIS, 2022)
PT. Mustikarama Citraperdana is a company engaged in security and protection products as well as storage solutions that have the SARGENTRACK trademark. In marketing its products, PT. Mustikarama Citraperdana uses a media in the form of a website with the address www.sargentrack.com. However, there are 2 (two) problems on the website, namely the lack of website visitors, and the search engine search results based on the targeted keywords are not in the top position or the first page which results in the website's popularity decreasing. Based on this, it is necessary to do an analysis of the SARGENTRACK website in order to increase the value of the website and be in the top position or first page on search engines. The method used is the SEO method. After SEO is implemented, the site's position in Google's SERP will be tested for several weeks to see how SEO techniques develop. The expected results in the application of the SEO method are able to increase the value of the website SERP (Search Engine Result Pages) on search engines and successfully indexed to the first page by Google.